Initial response in antibacterial activity of orthopaedic metal implant coated with silver composite - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Sha'ban, Munirah (2017)
Introduction: The objective of this study was to investigate the potential effect of silver coated orthopaedic metal implant against biofilm-producing staphylococcus aureus through an in vitro experimental setting. Our hypothesis was that orthopaedic implant coated with silver would exert both bacteriostatic and bactericidal effects against staphylococcus aureus. Materials & methods: The silver coated plate was soaked with 200ml of phosphate buffered saline (PBS) in shaking water bath at 37˚C for silver release preparation. 5.0ml solution was collected at 1-, 3-, 24-, 48-, 168-, 336- and 504-hour time point for analyses. Bacterial inoculation was smeared on sterile nutrient agar media. Plain discs placement were loaded on the surface of nutrient agar. 20µl silver release solution in each assessment was loaded on the plain disc. 20µl of PBS also was loaded on the plain disc and used as control. All samples were incubated at 37 ˚C for 24 hours for bacterial culture under aerobic condition. The samples were incubated up to 168 hours under the same conditions for assessment. The antibacterial effect was evaluated based on the diameter of inhibition zone using disc diffusion test.